Efficiency of PCR marker F311 of the SGR gene in assessing the resistance of cucumber lines to downy mildew Pseudoperonospora cubensis - D. D. Teplyakova (Овощи России, 2023)
Relevance. Downy mildew (Pseudoperonospora cubensis) is a serious problem when growing cucumber both in open and protected ground. One of the most effective methods of combating Pseudoperonospora cubensis is the cultivation of genetically resistant hybrids. To create them, it is necessary to include genetic markers in breeding work that speed up and increase the accuracy of selection. The F311 genetic marker of the SGR gene provides resistance to the destruction of chlorophyll, which can significantly reduce the rate of development of downy mildew, as well as preserve the growth and development of plants.Material and methods. In 2021-2022, at the Crimean Breeding Center, parental lines of cucumbers were studied in spring rotation in open ground. A total of 39 samples were studied. Their resistance to downy mildew against a natural infectious background was assessed on a 5-point scale. Hybrids were chosen as standards: St resistance – Phoenix+, St susceptibility – F1 Tchaikovsky, which scored the maximum damage score during visual assessment, All studied material was tested for the presence of the SGR gene for resistance to chlorophyll destruction using PCR analysis using the F311 marker.Results. The operating efficiency of the F311 (SGR) marker under the conditions of this experiment was 87.2%. And the efficiency of using the F311 (SGR) marker for assessing resistance to Pseudoperonospora cubensis is 84.6%. Based on the results of the experiment, we can conclude that the use of the F311 (SGR) marker will significantly speed up the process of selection and creation of hybrids resistant to Pseudoperonospora cubensis with a complex of economically valuable traits.